Patterning of the Drosophila retina by the morphogenetic furrow - Warren, Jasmine; Kumar, Justin P. (Frontiers in Cell and Developmental Biology, 2023)
Pattern formation is the process by which cells within a homogeneous epithelial sheet acquire distinctive fates depending upon their relative spatial position to each other. Several proposals, starting with Alan Turing’s diffusion-reaction model, have been put forth over the last 70 years to describe how periodic patterns like those of vertebrate somites and skin hairs, mammalian molars, fish scales, and avian feather buds emerge during development. One of the best experimental systems for testing said models and identifying the gene regulatory networks that control pattern formation is the compound eye of the fruit fly, Drosophila melanogaster. Its cellular morphogenesis has been extensively studied for more than a century and hundreds of mutants that affect its development have been isolated. In this review we will focus on the morphogenetic furrow, a wave of differentiation that takes an initially homogeneous sheet of cells and converts it into an ordered array of unit eyes or ommatidia. Since the discovery of the furrow in 1976, positive and negative acting morphogens have been thought to be solely responsible for propagating the movement of the furrow across a motionless field of cells. However, a recent study has challenged this model and instead proposed that mechanical driven cell flow also contributes to retinal pattern formation. We will discuss both models and their impact on patterning.